Upper Gastrointestinal Bleeding Caused by Rupture of Pancreatic Pseudoaneurysms - Huong Tu Lam; Thang Dinh Nguyen; Phat Tan Ho; Ai Van Nguyen; Tuan Huynh Nhat Nguyen; Phuoc Van Le; Thong Duy Vo (Case Reports in Critical Care, 2023)
Pseudoaneurysm rupture in patients with pancreatitis is a rare but fatal etiology of upper gastrointestinal bleeding. We report a rare case of upper gastrointestinal bleeding in a patient who presented simultaneously with two pseudoaneurysms, a potential cause of severe gastrointestinal bleeding. Angiography was successfully performed with coil embolization of the target arteries and both pseudoaneurysmal sacs. The patient was discharged 9 days after admission without further events within a 3-month follow-up period.